Dynamics of the modulated electron beam in the inhomogeneous plasma barrier: kinetic effects - Anisimov, I.O.; Soloviova, M.J. (Вопросы атомной науки и техники, 2008)
Evolution of the modulated electron beam moving through the inhomogeneous plasma barrier with parameters corresponding to experimental conditions [1-2] is studied via computer simulation using PIC method. Electrons’ energy distribution function of the initially density modulated electron beam moving through the barrier with Gaussian plasma density profile is studied. Initial-boundary problem is solved, and results obtained are compared with results of experiments and previous simulations.